A lateral strain plasticity model for FRP confined concrete. (15th December 2016) - Piscesa, Bambang; Attard, Mario M.; Samani, Ali Khajeh
Abstract: This paper presents a plasticity constitutive formulation for actively and passively confined concrete. The loading surface is based on Menetrey and Willam's model with an additional frictional driver parameter. The frictional driver parameter controls the prediction of the peak stress and the residual stress level. The proposed flow rule has a plastic dilation rate control parameter which is a function of the restraining device or the local lateral modulus. A non-constant plastic dilation rate formulation is proposed to improve the prediction of the lateral strain behaviour of concrete. The proposed plastic dilation rate formulation is able to model plastic volumetric compaction caused by the use of very stiff confining devices, as well as the initial plastic compaction after the onset of localized cracking. Furthermore, the formulation is able to distinguish between active and passive confinement by monitoring the local lateral modulus. The accuracy of the proposed plastic dilation rate formulation is verified by comparison with experimental results for specimens subjected to either active or passive confinement from a variety of concrete strengths. The comparison between the proposed plasticity model and the experimental results for concrete under passive confinement (specimens with FRP confining material) was excellent.